Astrophysical constraints on a light spinless particle coupled to photons - Mori, F. [UNESP] (World Scientific Publishing, 1996)
We examine further astrophysical constraints on a light spinless particle coupled only to photons and proposed by Massó and Toldra. We consider constraints coming from measurements of extra galactic background and from ionization of HI clouds.